2019
DOI: 10.1177/0018578719888913
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of Lactated Ringer’s Injection With 94 Selected Intravenous Drugs During Simulated Y-site Administration

Abstract: Objective: To test the compatibility of intravenous (IV) lactated Ringer’s injection (LR) with 94 injectable (IV) drugs during simulated Y-site administration. Methods: Ninety-four IV drugs were investigated for compatibility with LR (Baxter). Each sample was prepared in duplicate and performed at room temperature. Two observers performed visual evaluation independently immediately upon mixing and then 15 minutes, 1 hour, 2 hours, 3 hours, and 4 hours after admixture. Another observer performed a particle coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Its safety is unquestioned, though drug incompatibilities exist (ciprofloxacin, diazepam, ketamine, lorazepam, nitroglycerin, phenytoin, and propofol). 15 So, modern resuscitation with crystalloids is still mainly with a solution developed by Sydney Ringer 140 years ago and modified by Alexis Hartmann, MD, 90 years ago. The use of Ringer's lactate has obviously decreased in recent years.…”
Section: Fluid Resuscitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Its safety is unquestioned, though drug incompatibilities exist (ciprofloxacin, diazepam, ketamine, lorazepam, nitroglycerin, phenytoin, and propofol). 15 So, modern resuscitation with crystalloids is still mainly with a solution developed by Sydney Ringer 140 years ago and modified by Alexis Hartmann, MD, 90 years ago. The use of Ringer's lactate has obviously decreased in recent years.…”
Section: Fluid Resuscitationmentioning
confidence: 99%
“…When compared with normal saline, the other crystalloid solution used for resuscitation, Ringer's lactate is hypotonic, less acidic (pH 6.5 vs. pH 5.5), and contains K + , Ca ++ , and lactate. Its safety is unquestioned, though drug incompatibilities exist (ciprofloxacin, diazepam, ketamine, lorazepam, nitroglycerin, phenytoin, and propofol) 15 …”
Section: Fluid Resuscitationmentioning
confidence: 99%
“…Balanced isotonic crystalloids can be co-administered with many medications, but some important drug incompatibilities have been identified. For example, Plasma-Lyte 148 is incompatible with pantoprazole, cyclosporine, and midazolam while LRS is incompatible with diazepam, ketamine, and cyclosporine ( 63 , 85 ).…”
Section: Fluid Choicementioning
confidence: 99%
“…A total of 2961 publications via search of databases and 35 publications from additional sources were assessed, and 35 manuscripts were identified for inclusion (Figure 1). Six studies were adjudicated as high risk of bias 20-25 and excluded from further analysis, for a final inclusion of 29 studies 26-54 (Supplementary Figures 1 and 2). Full characteristics of all included studies can be found in Supplementary Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the medications included in this review have only one unique assessment evaluated, which significantly limits generalizability. 46,48,50 Other medications were assessed in multiple different combinations but by only one study, which again limits external validity. 33,39,48 Recently the importance of utilizing balanced crystalloids instead of normal saline for resuscitation in critically ill patients has been emphasized to decrease the risk of hyperchloremic AKI, metabolic acidosis, and potentially mortality.…”
Section: Discussionmentioning
confidence: 99%